Rekontruksi Akibat Hukum atas Sikap Nabi saw. yang Meninggalkan Suatu Amalan Tertentu (Tark al-Nabi) - Bakhrul Huda (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Differences in punishing something happen among Muslim scholars. This is not only because of the way of view in terms of dalalah al-lafd -to understand the meaning contained in the word-, but the factor has not reached nass by the others or the other's way of view that’s the nass is invalid, also because of the problem of tark al-nabi -the attitude of the Prophet pbuh. which leaves doing something-is a vast field that also greatly supports the differences between moslems. This Terma of al-tark is one of the ways we understand and act on legal differences among Muslims. The author is interested in studying this term by library so that the results of this study could be one additional reading reference in drawing the conclusions of phenomena that occur today especially since there is a conservative dakwah disturbing spread in many social media. So we will know that the Prophet’s attitude of not doing in some cases not necessarily haram or even makhruh either in the realm of worship or culture if not supported with the other theorems.